KEPUTUSAN BISNIS DAN TANGGUNGJAWAB DIREKSI DALAM PRINSIP FIDUCIARY DUTIES PADA PERSEROAN TERBATAS - Muhayatsyah, Ali (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2019)
The main party charged with fiduciary duty is the board of directors. In UUPT No. 40/2007 it does not specifically regulate fiduciary duty but rather regulates general principles. From the general principle of fiduciary duty, directors in managing the company must pay attention to the interests of the company above other interests; directors must act in accordance with the aims and objectives of the company (intra vires), and pay attention to the limitations and restrictions determined by the law and the articles of association of the company. In carrying out their duties as directors, they are required to have in good faith and in full sense of responsibility; Directors must carry out their duties diligently, carefully, and smartly and skillfully. Keywords: Directors, Fiduciary Duty, Business Judgment Rule, Limited Liability Company, Abstrak Pihak utama yang dibebankan kewajiban fiduciary duty adalah direksi. Dalam UUPT Nomor 40 Tahun 2007 tidak mengatur secara khusus mengenai fiduciary duty tetapi mengatur prinsip-prinsip umumnya. Dari prinsip umum fiduciary duty makadireksi dalam mengurus perseroan harus memperhatikan kepentingan perseroan di atas kepentingan lainnya;direksi harus bertindak sesuai dengan maksud dan tujuan perseroan (intra vires), serta memperhatikan batasan dan larangan yang ditentukan UU dan anggaran dasar Perseroan. Dalam melaksanakan tugas sebagai direksi, diharuskan memiliki itikad baik (in good faith) dan tanggung jawab (in full sense of responsibility); Direksi harus melaksanakan tugasnya dengan rajin (diligently), penuh kehati-hatian (carefully), dan pintar serta terampil (skillfully). Kata kunci: Direksi, Fiduciary Duty, Business Judgement Rule, Perseroan Terbatas,